An Investigation into the Awareness, Knowledge and Attitude of Student Teachers towards Climate Change - Nayak, Jyotirmayee (INDIAN EDUCATIONAL REVIEW, 2011)
The purpose of the study was to understand the level of awareness, knowledge and attitude of student teachers towards climate change. Descriptive survey method was used to carry out the research study by taking sample from B.Ed. colleges of Mumbai and Navi-Mumbai region. The study revealed that though the student teachers of different stream i.e., Science, Commerce and Arts are aware of the problem of the climate change but they lack in having sufficient knowledge of climate change with regards to its causes and consequences. Also the study revealed that there is no significant difference in the knowledge of climate change of Science and Commerce student teachers. However, a significant difference was found between the student teachers of Science and Arts stream and also between Commerce and Arts stream. Further, the study reveals that there lies difference in the level of awareness, knowledge and attitude between the student teachers of Mumbai and Navi-Mumbai.